The Implementation of the Meaning of Ta‘zim Sya‘airillah in Digital Islamic Propagation: A Visual Analysis of Honoring Sacrificial Animals in YouTube Content - Muhammad Qudwatul Ibad; Fauzan Zenrif; Toriquddin Toriquddin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
In the digital era, the propagation (syiar) of the Qurban sacrifice has transformed from physical spaces to the stage of YouTube, creating the